Pest diagnosis expert system on chili plants using Forward Chaining method in the department of agriculture in Pagar Alam City - Septriani, Evy; Mukti, Yogi Isro (Institut Teknologi Dirgantara Adisutjipto, 2020)
This study aims to produce an expert system for diagnosing pests in chilies using the Forward Caining method. Chili is one of the basic needs of the community as a flavoring or flavor, but farmers often experience failure to harvest due to pest attacks on chili plants. The system development method used by Waterfall consists of four stages, namely Analysis, Design, Coding and Testing. Therefore, the researcher created an expert system for diagnosing pests in chilies using the Onlane Forward Chaining method. the benefits of this expert system for the city of Pagar Alam, especially for farmers, make it easy to find out the types of pests that attack and provide solutions to prevent pests from being planted in chilies like an expe